Current perspectives on treatment of hypertensive patients with chronic obstructive pulmonary disease - Chandy D; Aronow WS; Banach M (Dove Medical Press, 2013)
Dipak Chandy,1 Wilbert S Aronow,2 Maciej Banach3 1Division of Pulmonary, Critical Care and Sleep, 2Division of Cardiology, Department of Medicine, New York Medical College, Valhalla, NY, USA; 3Department of Hypertension, Medical University of Lodz, Lodz, Poland Abstract: Systemic hypertension and chronic obstructive pulmonary disease (COPD) frequently coexist in the same patient, especially in the elderly. Today, a wide variety of antihypertensive drugs with different mechanisms of action are available to the prescribing physician. In addition, combination drugs for hypertension are becoming increasingly popular. Certain antihypertensive drugs can affect pulmonary function. Therefore the management of such patients can present therapeutic challenges. We have examined the literature pertaining to the use of antihypertensive drugs in patients with systemic hypertension and coexisting COPD. Although data are often limited or of poor quality, we have attempted to review and then provide recommendations regarding the use of all the specific classes of antihypertensive drug therapies including combination drugs in patients with COPD. The antihypertensive agents reviewed include diuretics, aldosterone receptor blockers, beta blockers, combined alpha and beta blockers, angiotensin-converting enzyme inhibitors, angiotensin II antagonists, calcium channel blockers, alpha-1 blockers, centrally acting drugs, direct vasodilators, and combinations of these drugs. Of these classes, calcium channel blockers and angiotensin II antagonists appear to be the best initial choices if hypertension is the only indication for treatment. However, the limited data available on many of these drugs suggest that additional studies are needed to more precisely determine the best treatment choices in this widely prevalent patient group. Keywords: blood pressure, hypertension, COPD, treatment, antihypertensive drugs